Single-cell transcriptome analysis reveals elongation and ossification characteristics of antlers - Han, Ruobing; Wang, Qianghui; Li, Heping (Frontiers in Veterinary Science, 2025)
IntroductionAntlers are specialized bony appendages in mammals that exhibit the remarkable ability to periodically regenerate from the pedicles and then rapidly elongate to form bone. Previous studies have demonstrated that this intricate and precise biological process involves the coordination of multiple cell types, whose understanding is central to a wide range of research areas, particularly those investigating bone growth and mineralization. Recent studies have shed light on the cellular composition in the rapid elongation and regeneration of antlers. However, the differentiation trajectories of mesenchymal and cartilage tissues in the antler tip at the single-cell resolution remain to be elucidated.MethodsThe mesenchymal and cartilage tissues of a healthy 5-year-old male sika deer (Cervus nippon) were collected for single-cell RNA sequencing.ResultsWe generated a single-cell profile of the antler tip containing 11 distinct cell types. A novel transitional cell exhibiting multiple cellular characteristics was identified. A total of three putative differentiation trajectories were identified for antler elongation and ossification, revealing that stem-cell-like state cells have the potential to differentiate into multiple cell types, including chondroblasts, chondrocytes, mural cells, and endothelial cells. We emphasize that the elongation and ossification of antlers are coordinated by various cells, among which some vital ligand–receptor interaction pairs were identified to be shared by the vast majority of cell types, such as CADM1/CADM1, TGFB1/TGFBR3, LGR4/RSPO3, and HLA-C/FAM3C ligand–receptor interaction pairs.ConclusionTaken together, the present study provides insights into rapid antler elongation and ossification at single-cell resolution and deepens our understanding of the differentiation process of antlers.